Differences in Platelet α-granule Release between Normals and Immune Thrombocytopenic Patients and between Young and Old Platelets - Rinder, Henry M.; Tracey, Jayne B.; Recht, Michael; DeCastro, Laura; Rinder, Christine S.; McHugh, Colleen; Smith, Brian R. (Thrombosis and Haemostasis, 1998)
The risk of serious bleeding in patients with immune thrombocytopenic purpura (ITP) appears to be less than in comparably thrombocytopenic patients with megakaryocytic hypoplasia. It has been proposed that this difference is due to enhanced hemostatic activity of young platelets, which are increased in the circulation during ITP. We examined α-granule release in reticulated platelets (RP), which are thought to be the youngest circulating platelets, and in older non-reticulated platelets (non-RP) in normal human controls and ITP patients. Normal controls had a mean RP of 7%, compared with 42% in ITP patients. The mean concentration of thrombin receptor agonist peptide (TRAP) causing 50% of control RP to express CD62P (EC50) was 0.82 ± 0.08 μM (SEM), significantly higher than the TRAP CD62P EC50 for RP in ITP, 0.57 ± 0.06 uM (p = 0.04). Similarly, the TRAP EC 50 for non-RP in controls, 0.84 ± 0.09 μM, was significantly higher than in ITP, 0.56 ± 0.07 μM (p = 0.03), suggesting that all platelets in ITP have an enhanced α-granule threshold response to TRAP compared with controls, while RP and older platelets within each patient group have similar threshold sensitivities to TRAP. By contrast, high-dose TRAP caused RP to express twice as much mean and total CD62P as non-RP in both ITP patients and controls (p <0.05 for both comparisons). We conclude that compared with controls, all platelets in ITP are primed to undergo α-granule release to TRAP, while in both ITP and controls, the newly circulating, reticulated platelets have the potential to contribute greater amounts of CD62P surface ligand compared with older platelets (non-RP) after stimulation. Both the increased RP% and enhanced platelet response to agonist in ITP may contribute to maintenance of hemostasis despite thrombocytopenia.